IOS 6 programming : pushing the limits : advanced application development for Apple iPhone, iPad, and iPod Touch - Napier, Robert (Pushing the Limits., 2013)
Learn to build extraordinary apps for iPhone, iPad, and iPod touch iOS is the hottest development platform around, and iOS 6 adds a new and deeper dimension to explore. This guide offers serious information for serious programmers who know the basics and are ready to dive into the advanced features of iOS. You'll learn to create killer apps for the iPad, iPhone, and iPod touch, including how to maximize performance and make more money from your apps with in-app purchases. Topics covered include security, multitasking, running on multiple platforms, blocks and functional program.